Additive interaction between potentially modifiable risk factors and ethnicity among individuals in the Han, Tujia and Miao populations with first-ever ischaemic stroke - Na Zhang; Xinrui Wu; Mengyuan Tian; Xiaolei Wang; Jian Ding; Yong Tian; Chengcai Liang; Zhi Zeng; Hua Xiang; Hongzhuan Tan (BMC, 2021)
Abstract Background As a country with one-fifth of the global population, China has experienced explosive growth in ischaemic stroke (IS) burden with significant ethnic and geographic disparities. The aim of this study was to examine the differences in potentially modifiable risk factors for ischaemic stroke among the Han population and two ethnic minorities (Tujia and Miao). Methods A case-control study was conducted with 324 cases of first-ever ischaemic stroke from the hospitals of the Xiangxi Tujia and Miao Autonomous Prefecture and 394 controls from communities covering the same area between May 1, 2018, and April 30, 2019. Structured questionnaires were administered, and physical examinations were performed in the same manner for cases and controls. Univariate and multivariate logistic regression analyses with adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were used to examine the association between risk factors and ischaemic stroke. An additive model was used to study the interaction between the modifiable risk factors and ethnicity with R software. Results Higher high-sensitivity C-reactive protein levels (OR 50.54, 95%CI 29.76-85.85), higher monthly family income (4.18, 2.40-7.28), increased frequency of hot pot consumption (2.90, 1.21-6.93), diabetes mellitus (2.62, 1.48-4.62), a higher apolipoprotein (Apo)B/ApoA1 ratio (2.60, 1.39-4.85), hypertension (2.52, 1.45-4.40) and moderate-intensity physical activity (0.50, 0.28-0.89) were associated with ischaemic stroke. There was an additive interaction between the ApoB/ApoA1 ratio and ethnicity in the Tujia and Miao populations with first-ever ischaemic stroke (the relative excess risk due to the interaction was 5.75, 95% CI 0.58 ~ 10.92; the attributable proportion due to the interaction was 0.65, 95% CI 0.38 ~ 0.91; the synergy index was 3.66, 95% CI 1.35 ~ 9.93). Conclusions This is the first case-control study examining modifiable risk factors for ischaemic stroke among the Han population and two ethnic minorities (Tujia and Miao) in China. Some differences were observed in the impact of risk factors among these ethnic groups. Our results may help interpret health-related data, including surveillance and research, when developing strategies for stroke prevention.